Control Social Engineering Security and Spear Phishing Attacks with Technology Solutions in Organizations - Taresa Vindy Oktavia; A Widjajarto; Muhammad Fathinuddin (Publikasi Indonesia, 2025)
In the current digital era, protecting information and being alert to the risk of data leaks is very important, especially for confidential data. Efforts to maintain the confidentiality of this information can use appropriate technology to prevent potential security threats. Using Open Source Intelligence (OSINT) can play a role in reducing the risk of phishing attacks by utilizing technology-based methods that involve social engineering activities and implementing spear phishing experiments via email content. This is useful for identifying security weaknesses that must be fixed. This research includes the application of OSINT, social engineering tools, and email content. Experiments involving OSINT and phishing attacks are depicted using Data Flow Diagrams (DFD) to show the flow of attacks carried out. Furthermore, the phishing attack is used as a basis for designing technology-based mitigation. This mitigation involves two technologies, namely email filters on email servers and two-factor authentication (2FA) for websites that are targets of phishing attacks. The addition of the two-factor authentication feature can be done because the target website has input in the form of an account and password text box.